Urinary Ethics in the Perspective of Hadith: (Analysis of the Contradictions of the Prophet's Hadith) - Purwantoro (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Backgound. The ethics of defecating in Islam are not only related to physical cleanliness, but also include the spiritual and social dimensions of Muslims. The hadiths of the Prophet Muhammad SAW provide clear guidance on the procedures and manners of defecating, which aim to maintain cleanliness, health, and social harmony. Although textually we often encounter contradictions between hadits mukhtalif the ethics of defecating. Aim. This article aims to analyze the ethics of defecating taught in the hadith, especially hadiths that textually appear to be mukhtalif. The author analyzes the main principles contained therein, and explores the relevance of these teachings in modern life. Methods. With a textual and contekstual analysis approach to relevant hadiths. This article will reveal how important it is to interpret hadith contextually, and how to understand the mukhtalif hadiths. Results. The hadith of the Prophet Muhammad SAW shows the Islamic religion's concern for cleanliness, politeness, and respect for certain places. After conducting in-depth research, it was found that there were no contradictions between the hadiths were found.